Measuring the Relationship Between Service Quality Delivery and Customer Satisfaction of Rural Banks in India: A Factor-Specific Approach - Ahmed, Jaynal Uddin; Momin, Chelsea Ch.; Mpanme, Ditalak; Ahmed, Nazim Uddin (International Finance and Banking, 2024)
The connection between service quality and customer satisfaction has acknowledged considerable theoretical and research attention over the years. But the nature of the precise relationship between service quality and customer satisfaction is still concealed with ambiguity. The present research article aims to examine the level of customers’ satisfaction on the delivery of bank services and to measure the relationship between customers’ satisfaction and services offered by rural banks in India. The study has considered 63 branches out of 94 branches of Meghalaya rural bank and a total of 400 customers who are directly associated with the banks i.e., at least having one account with the banks using the purposive sampling method. The opinion of the respondents on the selected variables indicating satisfaction/dissatisfaction level was measured on a Likert scale. The data have been analysed through statistical techniques such as descriptive statistics, correlations analysis and regression analysis using Statistical Package for Social Sciences (SPSS), Version 21. The analysis indicates that there is an inter-relationship between the influencing factors namely intangible infrastructure, reliability, assurance, responsiveness and empathy, and also verifies that the variables displayed a linear relationship relating to the constructs to each other. The analysis also reveals that tangible infrastructure, reliability and empathy are significant predictors of the level of customer satisfaction while assurance and responsiveness are not appropriate predictors of customer satisfaction levels. The paper recommended that the bank should ensure its commitment towards assurance and responsiveness to build the trust of the customers towards the banks. It is expected that the study will enable the bank management to get a comprehensive choice of empowering their strategies effectively to reach out to the customers.